IS BRAIN CHOLESTEROL THE MISSING CULPRIT IN DRUG ADDICTION? - Hinshaw, Tyler (Wake Forest University, 2017)
Chronic psychostimulant exposure alters the signaling of G-protein coupled receptors (GPCRs), which is associated with drug relapse. Although the molecular mechanisms remain unknown, scant evidence suggests a potential role of membrane lipids especially cholesterol in regulation of psychostimulant-mediated GPCR signaling. Plasma membrane is organized into cholesterol-enriched lipid raft and non-lipid raft microdomains. GPCRs and their interactinG-proteins are localized in lipid rafts or non-lipid rafts in a receptor-dependent manner. Depletion of cholesterol disrupts certain GPCR function. This study investigates the effects of amphetamine (AMPH) self-administration on cholesterol content, lipid raft localization of Gα subunits and effectors, and receptor-stimulated G-protein downstream signaling in rat striatum. We found that striatal cholesterol levels were significantly reduced following both 5 and 14 days of AMPH self-administration. Using sucrose density gradient fractionation, we found that more Gα subunits (Gαi1/2/3, Gαo and Gαq) were translocated into lipid rafts whereas their effectors such as adenylyl cyclase (AC) and phospholipase Cβ (PLCβ) remained in non-lipid rafts. Importantly, translocation of Gα subunit isoforms between lipid rafts and non-lipid rafts has functional consequence on receptor-mediated G-protein signaling. The ability of Gαi/o-coupled dopamine D2/D3 receptors and serotonin 5-HT1A/1B receptors to inhibit AC activity is reduced in AMPH self-administering rats. Moreover, the ability of Gαq-coupled mGluR1/5, but not serotonin 5-HT2A/2C receptors, to stimulate PLCβ activity is also decreased in AMPH self-administering rats. These data suggest an association of cholesterol content with Gα subunit compartmentalization and signaling. Using neuroblastoma N2A cells stably expressing the short form of dopamine D2 receptors, we found that membrane cholesterol depletion with methyl-β-cyclodextrin directly caused Gαi2 movement into lipid rafts. Furthermore, the ability of dopamine D2 receptors to inhibit Gαi/o-mediated AC activity is reduced following cholesterol depletion. This is the first observation of AMPH-induced reduction in cholesterol content and G-protein movement between lipid rafts and non-lipid rafts. These findings point to cholesterol as a regulator of GPCR signaling in psychostimulant abuse.
Keywords: Amphetamine; Cholesterol; G-Proteins; Striatum